GIS-Based Land Suitability Analysis for a Tourism Airport in Bulukumba Regency, South Sulawesi, Indonesia - Dg Bau, Qadriathi; Adisasmita, Sakti Adji; Kamin, Yusi; Abdullah, Sulaiman; Basuki, Imam (Department of Civil and Environmental Engineering, Faculty of Engineering, Universitas Gadjah Mada, 2026)
Bulukumba Regency is renowned for its rich cultural heritage and diverse tourism potential, positioning it as a prominent destination at both national and international levels. However, limited transportation infrastructure—particularly the absence of a local airport—presents significant accessibility challenges. Travel from Sultan Hasanuddin International Airport to Bulukumba requires approximately six hours by land, which hinders tourism development. This study aims to address this gap by: (1) identifying the most suitable location for a tourism-focused airport using the Analytical Hierarchy Process (AHP), and (2) generating a spatial suitability map for potential airport sites through GIS-based analysis. A weighted hierarchical quantitative approach was employed, using selection criteria based on the Indonesian Ministry of Transportation Regulation No. PM 55/2023 outlines seven key aspects and associated sub-criteria for airport site selection. Each criterion was assigned a weight reflecting its relative importance, followed by AHP analysis to determine the priority values of sub-criteria. The resulting weights were integrated into a Geographic Information System (GIS) to conduct spatial overlay analysis and identify optimal locations. The analysis identified Ara Village and Caramming Village as the most suitable locations for a tourism airport, with the highest composite score (226). Three alternative airport site maps were also produced, offering spatial options for future development. This study provides crucial insights to improve regional connectivity and support sustainable tourism growth in Bulukumba Regency.